Information needs in syndicated lending - Manickam Ananthakannan. (2010)
The objective of this study is to identify the information needs in syndicated lending. It attempts to enrich our understanding of the role that information plays in syndicated lending. This is yet another attempt to highlight the role of an information centre/library within a banking institution. There are three key players in syndicated lending. They are the borrowers, the lead managers and the participant banks. The lead managers are responsible for bringing the borrowers and the participant banks together to arrange a successful loan syndication. In this study, the role of a lead manager has been examined to identify its involvement in the various stages of syndicated lending. The information needs in syndicated lending have also been explored in the context of the lead manager's primary role in syndicated lending.